THE INTERNAL AUDIT IN LIGHT OF ARTIFICIAL INTELLIGENCE: AN EXPLORATORY STUDY IN THE IRAQI ENVIRONMENT - Enas Nusrat Suleiman (Scholar Express Journals, 2023)
The study aims to illustrate the concept of internal audit as an independent variable with its three dimensions (objectivity and independence, efficiency and technical qualifications, doing professional care) in the light of artificial intelligence as a dependent variable with its three dimensions (experienced systems, representation of knowledge and inference, and automatic learning) and then, determining the relationship of correlation and effect between them. In order to achieve the objectives of the research, a questionnaire that consists of (30) items was designed, and in the light of it, data were collected and analyzed, and hypotheses tested by using the statistical program (SPSS). The study sample consisted of (60) individuals in private banks. Several statistical tools and methods were used to achieve the research objectives, including: frequencies, percentages, arithmetic means, standard deviations, correlation coefficient and regression analysis. The most important results of the research were: the presence of a significant correlation relationship between the two variables, and a strong effect between internal audit and artificial intelligence.
Keywords: Internal Audit; Artificial Intelligence.